2007
DOI: 10.1038/sj.ijo.0803715
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on the musculoskeletal system

Abstract: Obesity is associated with a range of disabling musculoskeletal conditions in adults. As the prevalence of obesity increases, the societal burden of these chronic musculosketelal conditions, in terms of disability, health-related quality of life, and health-care costs, also increases. Research exploring the nature and strength of the associations between obesity and musculoskeletal conditions is accumulating, providing a better understanding of underlying mechanisms. Weight reduction is important in ameliorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
232
2
20

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(293 citation statements)
references
References 154 publications
8
232
2
20
Order By: Relevance
“…9,32 An earlier study indicated that obesity has a significant impact on the musculoskeletal system. 33 Obese individuals are more likely to have weak back or abdominal muscles because of their additional body weight. 34 Thus, there is a greater likelihood of increased stress on the musculoskeletal system; in addition, their own strength has decreased as they have gained additional mass.…”
Section: Discussionmentioning
confidence: 99%
“…9,32 An earlier study indicated that obesity has a significant impact on the musculoskeletal system. 33 Obese individuals are more likely to have weak back or abdominal muscles because of their additional body weight. 34 Thus, there is a greater likelihood of increased stress on the musculoskeletal system; in addition, their own strength has decreased as they have gained additional mass.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of musculoskeletal symptoms in the knees of obese people has been well-established in the literature (5,21). It has been demonstrated that weight gain is associated with adverse effects on the knees, such as pain, stiffness and functional changes (22).…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence of musculoskeletal symptoms affecting mainly the lower limbs has been reported in obese individuals (4,5). Some of these symptoms manifest as joint discomfort caused mainly by excess weight, which can overload the musculoskeletal structures responsible for stabilizing and moving the body (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Consequences of the obesity epidemic are an increase in the occurrence of cardiovascular diseases, diabetes, musculoskeletal disorders, such as osteoarthritis of knee and hip, and certain types of cancers. 3,4 Cardiovascular diseases are the main cause of death worldwide and diabetes has rapidly grown into a global epidemic. 5 Therefore, overweight is a serious threat to public health.…”
Section: Introductionmentioning
confidence: 99%